Cumulative Rheumatic Inflammation Modulates the Bone–Vascular Axis and Risk of Coronary Calcification. Issue 11 (4th June 2019) - Chan, Yap‐Hang; Ngai, Michael Cheong; Chen, Yan; Wu, Mei‐Zhen; Yu, Yu‐Juan; Zhen, Zhe; Lai, Kevin; Cheung, Tommy; Ho, Lai‐Ming; Chung, Ho‐Yin; Lau, Chak‐Sing; Tse, Hung‐Fat; et al.
Abstract : Background: Rheumatic diseases are related to both abnormal bone turnover and atherogenesis, but a mechanistic link was missing. Methods and Results: We investigated the effect of cumulative rheumatic inflammation (CRI) on risk of coronary calcification in a retrospective cohort of 145 rheumatoid arthritis patients. A time‐adjusted aggregate CRI score was derived by conglomerating all quarterly biomarker encounters of serum C‐reactive protein over 60 months immediately preceding computed tomography coronary angiography. Flow cytometry was performed to measure the osteocalcin‐positive (OCN + ) CD34 + KDR + and OCN + CD34 + circulating endothelial progenitor cells (EPCs). Conventional early circulating EPCs CD34 + CD133 + KDR + was determined. Coronary calcification was defined as any Agatston score >0. 50% of patients (n=72/145) had coronary calcification. CRI score was associated with presence of coronary calcification ( P =0.004) (multivariable‐adjusted: highest versus lowest quartile: odds ratio=5.6 [95% CI 1.1–28.9], P =0.041). Receiver operating characteristics curve revealed divergent behavior of OCN‐expressing circulating EPCs (OCN + CD34 + EPCs: area under the curve=0.60, P =0.034; OCN + CD34 + KDR + EPCs: area under the curve=0.59, P =0.053, positive predictors) versus conventional early EPCs (CD34 + CD133 + KDR + : area under the curve=0.60, P =0.034, negative predictor) for coronary calcification, which persisted after multivariable adjustments (OCN + CD34 + KDR + [>75th percentile]: odds ratio=7.2 [95% CI 1.8–27.9], P =0.005; OCN + CD34 + EPCs [>75th percentile]: odds ratio=6.0 [95% CI 1.5–23.3], P =0.010; CD34 + CD133 + KDR + [>75th percentile: odds ratio=0.3 [95% CI 0.1–1.0], P =0.053). Intriguingly, the CRI score was associated with increased OCN + CD34 + EPCs (highest versus lowest quartile: B=+25.6 [95% CI 0.8–50.5] [×10 3 /mL peripheral blood], P =0.043), but reduced CD34 + CD133 + KDR + EPCs (highest versus lowest quartile: B=−16.2 [95% CI −31.5 to −0.9], P =0.038). Conclusions: Preceding 60 months of CRI is associated with increased risk of coronary calcification and altered OCN expression in circulating EPCs.